PENGARUH CURRENT RATIO, NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN DI BURSA EFEK INDONESIA: Current Ratio; Earning Per Share; Net Profit Margin; Stock Price - Darwin, Darwin; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2023)
The coal mining industry serves as an indicator to support the Indonesian economy. The increasing number of investors seeking to invest in the coal mining sector in the Indonesian Stock Exchange contributes to the country's economy through tax revenue generated from coal sales. Therefore, investors seek companies with good performance by analyzing financial statements and ratios that influence stock prices. The purpose of this research is to determine the influence of current ratio, net profit margin, and earning per share on stock prices in coal mining companies listed on the Indonesian Stock Exchange from 2018 to 2022. The research uses purposive sampling, resulting in 20 companies and financial reports for 5 periods that meet the criteria. The hypothesis testing using t-tests shows that current ratio (X1) has a negative and insignificant effect on stock prices (Y), net profit margin (X2) has a significant negative effect on stock prices (Y), and earning per share (X3) has a significant positive effect on stock prices (Y). Furthermore, the F-test indicates that the combined influence of current ratio, net profit margin, and earning per share significantly affect stock prices.